Teams Games Tournament Learning Model; Efforts in Improving Students' Way of Thinking - Febriyanti Ghayatul Qushwa; Anis Sulala (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
The aims of this study was to explore the effectiveness of the Teams Games Tournament (TGT) learning model in increasing students' cognitive engagement and reducing boredom during classroom learning. Using the Classroom Action Research (CAR) methodology, this study involved 24 female students from class VIII B Regular. Data collection used pre-test and post-test assessments to evaluate learning progress. The intervention followed four procedural stages: planning, action implementation, observation/evaluation, and reflection. Initial findings revealed suboptimal student performance, with only 8.3% achieving the learning mastery standard (mean score: 56.91). After implementing the TGT model in the second cycle, significant improvements were observed. The students' average score increased to 80.25, and 70.83% of students met the learning mastery threshold. These results demonstrate the capacity of the TGT model to stimulate active student participation, encourage cooperative learning, and improve critical thinking skills. This study underscores the importance of implementing a student-centered pedagogical approach to maximize educational outcomes and engagement, especially in a complex subject such as Tajwid Science. This study provides valuable insights for educators seeking to develop interactive and inclusive classroom environments. While the results are promising, further research is recommended to examine the adaptability of the TGT model across different subject areas and student demographics.